Pengaruh Kepemimpinan Pengurus terhadap Kinerja Karyawan (Studi kasus pada Koperasi BMT Ibnu Sina Bandung) - Dindin Burhanudin; Desi Melani (J-Coop : Journal of Co-operative, 2026)
This study aimed to analyze the leadership of the chairperson of the cooperative board and its role in improving employee performance at BMT Ibnu Sina Cooperative, Bandung. Leadership plays a strategic role in cooperative management because it influences work motivation, task effectiveness, and the achievement of organizational goals. This research employed a case study method with a descriptive qualitative approach. Research data were collected through observation, interviews, questionnaires, and documentation involving the cooperative board members and employees. Data analysis was conducted by examining leadership style indicators consisting of authoritarian, participative, and delegative leadership, as well as employee performance indicators including work quality, work quantity, task execution, and responsibility. The results showed that the leadership style applied by the chairperson of BMT Ibnu Sina Cooperative tended to be participative leadership. The chairperson involved employees in decision-making processes, provided opportunities for employees to express suggestions and opinions, and fostered open and harmonious communication. The implementation of participative leadership had a positive impact on employee performance improvement. This was reflected in good work quality and quantity, employees’ ability to perform tasks accurately, and a high level of responsibility toward assigned duties. The findings indicated that participative leadership played an important role in enhancing employee performance and supporting the sustainability of cooperative business activities. Therefore, cooperative board members were encouraged to maintain and further develop participative leadership practices in order to improve employee performance, strengthen organizational effectiveness, and enhance the welfare of cooperative members in a sustainable manner.